Communication Strategy Of Subscription Broadcasting Institutions (LPB) In Responding To The Implementation Of Analog Switch Off (ASO) - Afrianto, Hendra; Angelita, Gloria (LPPM Universitas PGRI Sumatera Barat, 2024)
The development of communication technology always increases rapidly over time. This happens to technology related to the internet and non-internet. One of the things carried out by the Indonesian Government is broadcast migration or switching TV broadcasts from analog to digital, or what is known as analog switch off (ASO). The transition from broadcasting to digital has become a necessity for broadcasters in all parts of the world. Indonesia is one of the countries that lags behind countries in Southeast Asia in implementing ASO. Because Indonesia will only stop broadcasting analog TV on November 2, 2022. While neighboring countries such as Brunei Darussalam implemented it in 2017, Singapore and Malaysia implemented it in 2019. The first research objective was to analyze the implementation of vertical communication strategies in optimizing company services, the second was to analyze the implementation of ASO in maintaining customer attraction. This research was conducted using a descriptive qualitative approach with post positivism methods. The research results are in accordance with the research objectives. LPB Pro Vision implements a vertical communication strategy well, where at all times this vertical communication is always well established, as evidenced by many other LPBs that have closed while Pro Vision is still able to survive. In the second research objective, Pro Vision as a whole still applies analog broadcasting, in maintaining customers service and broadcast quality are always prioritized.